Microgrids and active distribution networks - Chowdhury, S. (IET renewable energy series, 2009)
A companion to Embedded Generation by Nick Jenkins and his colleagues, this book is a timely publication for an evolving industry. Renewable energy, ancillary services and deregulation of the power industry are changing electricity delivery networks. Microgrids, smartgrids and active distribution networks require a sound understanding of the basic concepts, generation technologies, impacts, operation, control and management, economic viability and market participation involved in grid integration.